The Influence of Project Methods to Develop the Naturalist Intelligence of Children - Rezi Lestya (Research Psychologie, Orientation et Conseil, 2024)
This research was motivated by the low interest of children to care for plants, the lack of concern for plants, the absence of the use of project methods in growing plants. This can be seen from the low awareness of children towards the environment, where children lack interest in maintaining and caring for plants due to the method that is often used by teachers is more of a question and answer method and assignment. So researchers use a different method from the method used usually in Harapan Bunda Kindergarten, which is using the project method which is a learning model that can help children know, and understand in reality. This study aims to determine the influence of project methods to develop children's naturalist intelligence in TK Harapan Bunda Pagaruyung, Tanjung Emas District, Tanah Datar Regency. The study used a quantitative approach with experimental methods, pre-experimental research design with the type of one-geoup pretest-posttest design. In this study, the population was the entire number of children in Tk Harapan Bunda Pagaruyung, Tanjung Emas District, Tanah Datar Regency consisting of 20 people whose sample was 10 people. The treatment given is to use the project method media in developing naturalist intelligence in children. The results showed that the average pre-test result was 0.85. After carrying out the treatment, there was an improvement seen from the post-test results which averaged 11.90. To test the significance of t0 by comparing t0 with tt at the level of significance of 1%, namely tt = 3.30, it can be known that t0 is greater than tt 3.30>3.25. Thus, it means that there is a significant difference between pre-test and post-test in experiments. Thus, the project method affects the knowledge of children's naturalist intelligence in TK Harapan Bunda Pagaruyung, Tanjung Emas District, Tanah Datar Regency.